PERJANJIAN TERAPEUTIK DITINJAU DARI PRINSIP INFORMED CONSENT ANTARA PASIEN DENGAN RUMAH SAKIT UMUM DAERAH DR. MOEWARDI SURAKARTA - , RETNO DYAH KHASANAH, Dr. Ari Hernawan, SH., M. Hum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was intended to identify obstacle in implementation of informed consent agreement between patient and Dr. Moewardi Hospital Surakarta and to identify resolution when there is default done by Dr. Moewardi Hospital in implementation of the informed consent between patient and the hospital. It was empiric research that relied on primary data as main source. Literary study was done, in which its result was analyzed qualitatively and presented descriptively. The results indicate that, first, obstacles in implementation of informed consent in Dr. Moewardi Hospital is patientâs low education level, physician laziness, patient not understanding physician words, and unclear information from physician to patient. Second, when there is default and law violation by physician in therapeutic transaction, peaceful settlement outside court is prioritized. This settlement is faster and does not disrupt hospital performance so hospital can still serve other patients that need help.